Capital Structure, Debt Tax Shield, and Firm Value -- A Propensity Score Matching Approach. - Wang, Taosha. (2017)
Abstract: The author investigates the effects of capital structure on a firm's market value using a set of econometric methodologies, including OLS, reversed OLS, instrumental variable method, generalized propensity score matching approach, and covariant balancing propensity score matching approach. The rest of this paper proceeds as follows. In Part B, I briefly explain the classic tax shield evaluation model constructed by Modigliani and Miller in 1963. Part III reviews the precedent literature of debt tax shield evaluation. Part IV introduces sample data and summarizes data characteristics. Part V and VI explain the econometric methodologies and interpret the regression results. Part VII concludes the research results. Part VIII points out potential future improvements to this study.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Economics.; Advisor: Marcelo Bianconi.; Committee: Jeffrey Zabel.; Keywords: Economics, and Finance.